Solution of optimal reactive power dispatch problem using pathfinder algorithm. Issue 11 (2nd November 2021) - Yapici, Hamza
Abstract : The optimal reactive power dispatch (ORPD) problem, as a subproblem of optimal power flow, has significant effects in providing reliability and economic operation. In this article, a modified version of the pathfinder algorithm (PFA), which is inspired by the collective movement of a swarm led by one member, is proposed for solving the ORPD problem. The objective of this study is to minimize the power losses by adjusting the control variables. Numerical analyses are performed on 57-bus and 118-bus power systems. To show the performance and effectiveness of the modified pathfinder algorithm (mPFA), some well-known methods are used for comparison. Statistical tests are performed to assess the consistency and ranking of the proposed method. The results show that the mPFA achieved competitive results and obtained a competitive ranking with statistical analyses. The simulations show that the proposed method could be a superior algorithm for solving the ORPD problem.